Interventional Study to Evaluate the Clinical Effects and Safety of the Nutraceutical Compound Brainup-10® in a Cohort of Patients with Alzheimer S Disease: A Multicenter, Randomized, Double-Blind, and Placebo-Controlled Trial - Sanchez-Olavarria, M (IOS Press BV, 2021)
Background: Clinically-evaluated nutraceuticals are candidates for Alzheimer s disease (AD) prevention and treatment. Phase I studies showed biological safety of the nutraceutical BrainUp-10®, while a pilot trial demonstrated efficacy for treatment. Cell studies demonstrated neuroprotection. BrainUp-10® blocks tau self-assembly. Apathy is the most common of behavioral alterations. Objective: The aim was to explore efficacy of BrainUp-10® in mitigating cognitive and behavioral symptoms and in providing life quality, in a cohort of Chilean patients with mild to moderate AD. Methods: The was a multicenter, randomized, double blind, placebo-controlled phase II clinical study in mild to moderate AD patients treated with BrainUp-10® daily, while controls received a placebo. Primary endpoint was Apathy (AES scale), while secondary endpoints included Mini-Mental State Examination (MMSE), Trail Making Test (TMT A and TMT B), and Neuropsychiatry Index (NPI). AD blood biomarkers were analyzed. Laboratory tests were applied to all subjects. Results: 82 patients were enrolled. The MMSE score improved significantly at week 24 compared to baseline with tendency to increase, which met the pre-defined superiority criteria. NPI scores improved, the same for caregiver distress at 12th week (p = 0.0557), and the alimentary response (p = 0.0333). Apathy tests showed a statistically significant decrease in group treated with BrainUp-10®, with p = 0.0321 at week 4 and p = 0.0480 at week 12 treatment. A marked decrease in homocysteine was shown with BrainUp-10® (p = 0.0222). Conclusion: Data show that BrainUp-10® produces a statistically significant improvement in apathy, ameliorating neuropsychiatric distress of patients. There were no compound-related adverse events. BrainUp-10® technology may enable patients to receive the benefits for their cognitive and behavioral problems. © 2021-IOS Press. All rights reserved.